2021
DOI: 10.1377/hlthaff.2020.00823
|View full text |Cite
|
Sign up to set email alerts
|

Disparities In Telehealth Use Among California Patients With Limited English Proficiency

Abstract: Telehealth services that allow remote communication between the patient and the clinical team are an emerging part of care delivery. Given language barriers, patients with limited English proficiency present a unique set of challenges in integrating telehealth and ensuring equity. Using data from 84,419 respondents in the 2015-18 California Health Interview Survey, we assessed the association between limited English proficiency and telehealth use (telephone and video visits) and evaluated the impact of telehea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
98
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(129 citation statements)
references
References 34 publications
10
98
3
1
Order By: Relevance
“…Additional reports in non‐genetics settings reveal similar disparities in traditionally underserved populations (Eberly et al., 2020; Ferguson et al., 2021). Racial disparities in telehealth services have been noted outside of the context of COVID‐19 (Butrick et al., 2015; Rodriguez et al., 2021), suggesting a need for additional investigation into the effects of telehealth on diverse patient populations. Although genetic counselors may prefer video, patient preference and outcomes should be the driver in deciding modality of telehealth delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Additional reports in non‐genetics settings reveal similar disparities in traditionally underserved populations (Eberly et al., 2020; Ferguson et al., 2021). Racial disparities in telehealth services have been noted outside of the context of COVID‐19 (Butrick et al., 2015; Rodriguez et al., 2021), suggesting a need for additional investigation into the effects of telehealth on diverse patient populations. Although genetic counselors may prefer video, patient preference and outcomes should be the driver in deciding modality of telehealth delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Less technologically savvy caregivers or those with limited English proficiency may have challenges implementing telehealth use instructions and/or prompts, especially if limited language options are provided. Recent large-scale health access research among adults demonstrates a significant ‘digital divide’ in that patients with limited English proficiency are less likely to use telehealth ( Rodriguez et al, 2021 ). Also, because younger children may have more difficulty focusing or engaging during virtual visits compared to older children ( Dueweke et al, 2020 ), family utilization of telehealth IPC compared to in-person services may vary based on age.…”
Section: Role Of Ipc and Telehealth In Access To Care During The Pandemicmentioning
confidence: 99%
“…Several studies have identified barriers to telehealth adoption such as limited English proficiency, lack of access to broadband internet and higher technical proficiency required to successfully integrate telehealth into clinical practice, and it is possible that these barriers may also have limited a more diverse racial representation of patient perspectives in our study. [22][23][24] Additional research into the magnitude of these disparate findings in telehealth feedback and utilization among different racial groups, and how these differences change over time is needed.…”
Section: The Impact Of Demographicsmentioning
confidence: 99%